El ingreso real promedio per cápita mensual y la pobreza monetaria en el Perú periodo 2017 - 2021 - Talledo Taricuarima, Ricardo Daniel (2023)
From the monetary point of view, a higher average income will help to successfully combat poverty levels, since it provides agents with resources to acquire the different goods and services that are required to live. The current study aims to determine the relationship between the average monthly real income per capita and monetary poverty in Peru, in the period 2017 - 2021. In line with the described purpose, this Correlational type and NonExperimental design research is elaborated. After the analysis of the results, the following conclusions are reached: the average monthly income is inversely related to poverty in the five-year period 2017 - 2021, a conclusion driven by the result of the Correlation Coefficient r = -0.986590466 and the Determination Coefficient R2 = 0.973360748; Therefore, if the average income increases, the consequence will be that poverty decreases, and vice versa. The study of the average income according to the geographical domain, places Metropolitan Lima and El Callao as the one that pays the best salaries, since the average income is S/. 1,278.80 per month, a value that exceeds the national average by 2.90%, and amounts to S/. 1,242.52. Most of the poor population aged 15 or over have secondary education, meaning 46.78% of the total. 50.09% of the population living in poverty have homes with dirt floors.